Health and illness beliefs among rural Malays : a case study in Kampung Pasir Panjang Pahang, Malaysia - Djhoanna S. Sugaran (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2005)
This study examines the health and illness beliefs among rural Malays in Kampung Pasir Panjang, Pahang, Malaysia. The objectives of the study are: to examine these beliefs and practices. Second, to examine their health seeking behaviour, including women, in relation to health and illness. Lastly, to identify the contributing factors that influence them to seek either traditional or hospital-based medical treatment. The study used a qualitative approach. Several methods of data collection were utilised. These included in-depth interviews, direct observation and secondary data. The findings of the study show that health does not only mean the ability to work or being physically healthy but it also covers the mental, spiritual and emotional dimensions. However, the perception of illness embodies the patient's subjective perception or sometimes the perception of those around him. The rural Malays believe that illness could be attributed to both the supernatural and non-supernatural forces. Furthermore, the study also shows that the different use of health resources among rural Malays in Kampung Pasir Panjang, Pahang is related to perceptions of the causes of illness and to the types of treatment, either traditional or modern. Rural Malays are gradually beginning to accept the role of hospital-based medicine in dealing with women's health and illness as in the case of pregnancy, childbirth and the postpartum period. At the same time, many Malay women hold strongly to traditional health-related rituals. It is clear that the rural Malays' concept of health and illness as well as their utilisation of health services in Kampung Pasir Panjang was largely influenced by their traditional belief system. However, there was also evidence of a slight decline in their continued conformity to traditional health practices due to exposure to current modern health practices